Parental determinants associated with early growth after the first year of life by race and ethnicity - Aguayo, Liliana; Chang, Cecilia; McCormack, Luke R.; Shalowitz, Madeleine U. (Frontiers in Pediatrics, 2023)
Objective: To investigate maternal and parental factors associated with changes in children’s body mass index percentile (BMI-P) from 12 to 24 months. Methods: Data from a prospective cohort of racially and ethnically diverse mothers, fathers, and children (n=245) were used. Changes in BMI-P from 12 to 24 months of age were examined using height and weight measurements collected at both times. Separate longitudinal mixed-effects models with maximum likelihood were introduced to examine the determinants introduced by mothers and determinants from both parents among all children, and by race and ethnicity. Results: Models that examine maternal and parental factors showed that children’s overall BMI-P decreased from 12 to 24 months (β= -4.85, 95% Confidence Interval (CI), -7.47, -2.23). Stratified tests showed that White children whose parents graduated high school, or completed a 4-year college degree or higher had greater decreases in BMI-P than White children born to parents with less than high school (β= -60.39, 95%CI, -115.05, -5.72; β= -61.49, 95%CI, -122.44, -0.53). Among Hispanic/Latinx children, mean BMI-P significantly decreased from 12 to 24 months (β= -7.12, 95%CI, -11.59, -2.64). Mother’s older age (β= 1.83, 95%CI, 0.29, 3.36) and child female sex (β= 11.21, 95%CI, 1.61, 20.82) were associated with gains in children’s BMI-P, while father’s older age was associated with decreases (β= -1.19, 95%CI, -2.30, -0.08). Conclusions: Parental determinants associated with children’s early growth varied by children’s sex and racial and ethnic background. Results highlight the importance of understanding racial and ethnic -specific obesity risks and including fathers in research.